Corrigendum to "The development of a digital-based learning evaluation tool using wordwall media for persuasive text material in elementary school" - Habib Maulana; Ngatmini; Muhtarom (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
In the original published version of this article, the author made a mistake in the order of the author names. The order of the author names is correct. The authors apologize for the error. The PDF versions of the article have been updated to correct the errors.